Modeling morphological structures with artificial intelligence: Derivatives and their meanings in the poem Burdah as an example - ALZYUDI, MARYAM; Alfugara , Saif Aldain (Al-Adab Journal, 2024)
The research presents a vision for a programming project using artificial intelligence to model the lexical structures of the morphological structures in the poem Burdah. The program analyzes the morphological units in the poem and returns them to the root, then reveals their morphological structure and their lexical and contextual connotations. In this study, the project was applied to the derivatives in the poem Burdah by Ka'b ibn Zuhair.The research aims to design an applied computer project that employs artificial intelligence to analyze morphological structures in Arabic poetry. So that artificial intelligence will be able to distinguish morphological structures and classify them into morphological sections such as: noun, verb, infinitives, and derivation of all kinds. It shows the lexical significance and context of morphological structures in poetry. So that the presented model becomes the nucleus of a project to model Arabic poetry, such as Al-Mu’allaqat, Al-Asma’iyat, Al-Mufadliyat, and ancient and modern poetry selections.The project has a strong importance in exploiting computer technologies and artificial intelligence to serve the Arabic language and presenting an open applied project for researchers that relies on computational linguistics in analyzing morphological structures in Arabic poetry.The research followed the basics of descriptive and computational linguistics through describing morphological structures and computer modeling them to achieve the research objectives.The project resulted in a computer application that uses artificial intelligence to process natural languages ​​by analyzing morphological structures in poetry and distinguishing their lexical and contextual connotations. It is a scalable version.